The Influence of Quality of Work Life and Personality on Organizational Commitment: A Case Study of Employees at UD Fatoni - Kesan Oktavian Ali; Mukmin Suryatni (Economics and Business Journal (ECBIS), 2026)
This study analyzes the influence of Quality of Work Life (QWL) and Personality (Big Five Personality Traits) on employee Organizational Commitment at UD Fatoni in Central Lombok, filling the empirical gap regarding the interaction of external and internal factors in the context of local SMEs prone to high turnover. The main objective is to prove the partial and simultaneous influence of both variables on employee commitment. An explanatory quantitative approach was applied with a population of 40 employees using census techniques, primary data through a valid and reliable 5-point Likert questionnaire (Cronbach's Alpha >0.60), and multiple linear regression analysis via IBM SPSS 25 after the classical assumption test was met. The results showed that QWL had no significant effect partially (sig=0.253>0.05; β=0.149), while Personality had a significant positive effect (sig=0.002<0.05; β=0.604), with a strong simultaneous effect (F=8.852; sig=0.001) explaining 32.4% of the commitment variance. In conclusion, internal factors dominate loyalty in trading SMEs, providing theoretical contributions to organizational behavior models and practical implications for management in personality assessment and optimization of basic QWL for sustainable retention.